Fluid type and volume reduce risk of post-ERCP pancreatitis and length of hospital stay in high-risk patients: a secondary analysis of the INDIEH trial - Talukdar, Rupjyoti; Kamal, Ayesha; Akshintala, Venkata S.; Goud, Rajesh; Lakhtakia, Sundeep; Ramchandani, Mohan K.; Tandan, Manu; Rao, G. V.; Nabi, Zaheer; Gupta, Rajesh; Kalapala, Rakesh; Basha, Jahangeer; Reddy, Manohar; Rai, Vijay K.; Goenka, Mahesh K; Sinha, Saroj; Kochhar, Rakesh; Elmunzer, B. Joseph; Khashab, Mouen A.; Kalloo, Anthony N.; Singh, Vikesh K.; Reddy, D. Nageshwar (Endoscopy International Open, 2020)
Background and study aims Impact of intravenous fluid administration on prophylaxis against post-endoscopic retrograde cholangiopancreatography pancreatitis (PEP) has not been rigorously evaluated among patients at high-risk for PEP.Patients and methods Effect of volume and type of fluid administered on PEP incidence was studied through a secondary analysis of high-risk patients who underwent endoscopic retrograde cholangopancreatography (ERCP) as a part of a randomized controlled trial in which all patients received rectal indomethacin. Periprocedural fluid was defined as fluid infused during and after ERCP.Results A total 960 patients were randomized during the trial, of whom 476 (49.6 %) received periprocedural fluids (mean volume = 1245 mL [± 629]). There was a trend towards a lower incidence of PEP in patients who received periprocedural fluid vs. those who did not (5.2 % vs. 8.0 %, P = 0.079). Among those receiving fluids, those who did not develop PEP received a higher mean volume of fluid vs. who developed PEP (1012 ± 725 mL vs. 752 ± 783 mL, P = 0.036). Among 174 patients (37 %) who received LR, patients who did not develop PEP received a higher mean volume of LR vs. those who developed PEP (570 ± 559 mL vs. 329 ± 356 mL, P = 0.006). Length of hospital stay decreased as the volume of periprocedural volume administration increased (r = 0.16, P < 0.001).Conclusion Higher fluid volume and lactated Ringerʼs use during the periprocedural period was associated with a decreased risk of PEP and length of hospital stay beyond rectal indomethacin in high risk patients.